2015
DOI: 10.1159/000368952
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Frailty in Geriatric Chronic Kidney Disease (CKD) Patients

Abstract: Frailty, which is a geriatric syndrome characterized by weakness, impaired mobility, balance, and minimal reserve, is highly prevalent in the renal population. While distinct from disability and comorbidity, some of the simplest and most clinically useful scales incorporate both the burden of medical symptoms and the effect on functional independence into the evaluation of frailty. In the renal population, the frailty phenotype has been shown to correlate with important outcomes such as hospitalization and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…1 Fried et al . defined frailty as a clinical syndrome in which 3 or more of the following were present: unintentional weight loss (10 lbs in the past year), self-reported exhaustion, weakness (grip strength), slow walking speed, and low physical activity.…”
Section: Frailty In the Ckd And Esrd Populationmentioning
confidence: 99%
“…1 Fried et al . defined frailty as a clinical syndrome in which 3 or more of the following were present: unintentional weight loss (10 lbs in the past year), self-reported exhaustion, weakness (grip strength), slow walking speed, and low physical activity.…”
Section: Frailty In the Ckd And Esrd Populationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The concept of frailty was primarily developed and has evolved to define geriatric syndromes, and chronological aging has been positively correlated with the increasing prevalence of the frail phenotype. 1,8 According to annual reports from the United States Renal Data System, 44.5% of end-stage renal disease (ESRD) patients undergoing dialysis are aged 65 years and older, 9 and the prevalence per million continues to increase more rapidly among older age groups. 10 The Korean nationwide ESRD patient registry reported that the mean age of these patients has sharply increased from 55.2 years in 2005 to 60.3 years in 2014, and the proportion of people with ESRD aged 65 years and older increased from 28% to 40.7% during the same period.…”
Section: Introductionmentioning
confidence: 99%
“…Although frailty is closely related to aging, it is not tantamount to aging and can be regarded as unsuccessful aging [5]. Occasionally, distinguishing frailty from comorbidity and disability is challenging; however, comorbidity is an etiological risk factor for frailty, while disability is an outcome of frailty [6] as postulated by gerontologists.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of comorbidity in frail individuals is higher than in those without frailty [4], among which, chronic kidney disease (CKD) is one of the most common diseases closely linked to frailty. Some studies found that the prevalence of frailty among patients with CKD or end-stage renal dis-BGR01491ease (ESRD) is 3-fold than that of patients without the disease [6]. Furthermore, frail patients undergoing hemodialysis were associated with a 2.6-fold higher risk of mortality and 1.43-fold higher risk of hospitalizations, independent of age, sex, comorbidity, and disability as compared to patients without frailty [11].…”
Section: Introductionmentioning
confidence: 99%